490 A high-fidelity globe and orbit surgical simulator for ophthalmologic surgical training. (April 2022) - Patel, Anuj; Hoskeri, Rishi; Reighard, Chelsea; Zopf, David
Abstract : OBJECTIVES/GOALS: Many ophthalmologic procedures involve operating on or manipulating the globe and bony orbit. Creating an anatomically accurate globe and orbit is of interest to improve surgical education for trainees. The purpose of this study was to create a high-fidelity globe and orbit model using synthetic materials and utilizing 3D-printing techniques. METHODS/STUDY POPULATION: A deidentified computed tomography scan of the head and neck was digitally rendered and segmented using Mimics and 3-Matic (Materialise NV, Belgium) to create a digital model of the bony orbit. The model was 3D printed using a stereolithographic 3D-printer (Formlabs, Somerville, MA). The globe was created by soaking a large water bead made from a water absorbing polymer (YIQUDUO, China) for 24 hours. The water bead was then coated consecutively with three layers of silicone (Smooth-On, Macungie, PA). A standard sausage casing was hydrated and encased around the water bead, representing the conjunctiva. The globe was placed into the 3D-printed orbit. An incision was made in the sausage casing and the defect was sutured by one ophthalmologist. RESULTS/ANTICIPATED RESULTS: The bony orbital anatomy was accurately represented by stereolithographic printing. The size and feel of the artificial globe was similar to that of an in vivo human globe. The incised sausage casing covering the globe was able to be manipulated and sutured using a 8-0 suture in a microsurgical environment. The sausage casing had high-fidelity characteristics of an in vivo human eye conjunctiva. DISCUSSION/SIGNIFICANCE: This model can be used for teaching of conjunctival suturing for ophthalmologic trainees. By use of easily obtained materials for the globe, this model has the potential to standardize teaching methods of challenging techniques, and can reduce the need for animal and human tissue procurement, which is the current standard for ophthalmologic teaching.